An Association of Cryptococcus Neoformans/C. gattii Genotype and HIV Status in Asia: A Systematic Review - Popchai Ngamskulrungroj, M.D.,Ph.D. (Siriraj Medical Journal, 2019)
Objective: It has been known that VNI molecular type of Cryptococcus neoformans/C. gattii is strongly associated with HIV patients. However, this paradigm has recently been challenged because of the high prevalence of VNI molecular type among non-HIV patients with cryptococcosis in East Asia. The purpose of this study was to answer the question: “Among cryptococcosis in Asia, is there an association between the genotype and the patient’s HIV status?”. Methods: Using a systematic review and meta-analysis study design, we included all relevant published data, which were any type of study designs, mainly studied clinical Cryptococcus neoformans/C. gattii strains isolated in Asia and had available molecular typing data. The primary study variables were Cryptococcus neoformans molecular type (VNI/non-VNI or ST5/non-ST5) and the HIV status of the patients at the time of diagnosis. We used a random-effects meta-analysis model to estimate the prevalence of HIV infection. Results: Sixteen retrospective descriptive studies during 2005 – 2018 (1,584 isolates) were included. Most of the cryptococcosis cases in East Asian countries were in non-HIV patients (72.4-81.8%), which differed from non-East Asian countries (2.6-28.3% associated with non-HIV patients). In East Asia, the HIV prevalence among VNI and ST5 infected patients ranged from 7.5% - 46.7% with the pooled prevalence of 19.8% (95% CI, 12.2% - 30.4%) and 5.3% - 52.4% with the pooled prevalence of 19.9% (95% CI, 6.9% - 45.3%), respectively. In non-East Asia, the HIV prevalence among VNI and ST5 infected patients ranged from 48.3% - 98.8% with the pooled prevalence of 81.9% (95% CI, 73.3% - 88.2%) and 52.3% - 88.0% with the pooled prevalence of 74.9% (95% CI, 40.7% - 92.8%), respectively. Statistical heterogeneity was high in both analyses with the I2 of 79-89% in all analyses. Conclusion: Our results confirmed the low prevalence of HIV prevalence among VNI and ST5 strains in East Asian countries. The emergence of high virulence genotype causing disease in non-HIV patient is highly unlikely, because the VNI and ST5 were associated with HIV patients in other Asian countries. It can be hypothesized that the low HIV prevalence among VNI and ST5 strains in East Asian is due to the high susceptibility to cryptococcosis of people living in this region. This requires further investigation.